PD-L1 expression in the microenvironment and the response to checkpoint inhibitors in head and neck squamous cell carcinoma. (1st January 2020) - Evrard, D.; Hourseau, M.; Couvelard, A.; Paradis, V.; Gauthier, H.; Raymond, E.; Halimi, C.; Barry, B.; Faivre, S.
ABSTRACT: In head and neck squamous cell carcinoma (HNSCC), data from studies using checkpoint-inhibiting antibodies that target programmed death 1 (PD-1) or its ligand the programmed death ligand 1 (PD-L1) demonstrated outstanding clinical activity. Translational investigations also suggested some correlations between therapeutic response and PD-L1 expression in tumor tissue. We comprehensively summarize results that have evaluated PD-L1 expression in HNSCC. We discuss flaws and strength of current PD-1/PD-L1 detection, quantification methods and the evaluation of PD-L1 as a prognostic and theragnostic biomarker. Understanding tumor microenvironment may help understanding resistance to checkpoint inhibitors, designing clinical trials that can exploit drug combinations.